Well‐Defined Imidazolium ABA Triblock Copolymers as Ionic‐Liquid‐Containing Electroactive Membranes. Issue 13 (26th May 2014) - Jangu, Chainika; Wang, Jing‐Han Helen; Wang, Dong; Sharick, Sharon; Heflin, James R.; Winey, Karen I.; Colby, Ralph H.; Long, Timothy E.
<x xml:space="preserve">Abstract</x> Nitroxide‐mediated polymerization (NMP) affords the synthesis of well‐defined ABA triblock copolymers with polystyrene external blocks and a charged poly(1‐methyl‐3‐(4‐vinylbenzyl)imidazolium bis(trifluoromethane sulfonyl)imide central block. Aqueous size‐exclusion chromatography (SEC) and 1H NMR spectroscopy studies confirm the control of the composition and block lengths for both the central and external blocks. Dynamic mechanical analysis (DMA) reveals a room temperature modulus suitable for fabricating these triblock copolymers into electroactive devices in the presence of an added ionic liquid. Dielectric relaxation spectroscopy (DRS) elucidates the ion‐transport properties of the ABA triblock copolymers with varied compositions. The ionic conductivity in these single‐ion conductors exhibits Vogel–Fulcher–Tammann (VFT) and Arrhenius temperature dependences, and electrode polarization (EP) analysis determines the number density of simultaneously conducting ions and their mobility. The actuators derived from these triblock copolymer membranes experience similar actuation speeds at an applied voltage of 4 V DC, as compared with benchmark Nafion membranes. These tailorable ABA block copolymers are promising candidates for ionic‐polymer device applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>